The current status of health literacy among caregivers of lung cancer patients:A cross-sectional survey - Lei Lei; Yuan Jiang; Gang Feng; Jing Li; Danfeng Wu; Xiaoyan Wang; Xiaojing Xue (PLoS ONE, 2026)
Aim This exploratory, hypothesis-generating study aimed to investigate the current status of cancer health literacy among lung cancer caregivers and to identify factors associated with their health literacy levels. The primary hypothesis was that caregivers would demonstrate sub optimal cancer health literacy. The primary endpoint was the total score on the Chinese Cancer Health Literacy Scale (C-CHLS). Secondary endpoints included scores on the Health Literacy of Caregivers Scale-Cancer (HLCS-C) and the identification of factors associated with caregivers’ health literacy. Background Health literacy, defined as an individual’s ability to acquire, comprehend, and utilize health-related information to make informed decisions for maintaining health, is a critical factor in cancer prevention and treatment. It significantly impacts individual health outcomes.While existing research primarily focuses on cancer patients,there is limited exploration into the health literacy of cancer caregivers, who play a vital role in patient support and care. Design A cross-sectional study. Methods Using convenience sampling, 198 caregivers of lung cancer patients receiving treatment at a tertiary hospital in Sichuan Province, China, from October 2024 to December 2024 were recruited. Data were collected using a general information questionnaire,health literacy of caregivers scale-cancer and Chinese cancer prevention and control literacy questionnaire. Data entry was performed using Microsoft Excel 2016, and statistical analysis was conducted using SPSS 26.0. Results Only 48.48% (n = 96) of caregivers demonstrated adequate health literacy. Multivariable analysis identified seven factors significantly associated with cancer health literacy (all p < 0.05): younger age (β = 0.187, t = 3.189), higher education level (β = 0.209, t = 2.784), professional occupation (β = 0.169, t = 2.144), better self-rated health (β = 0.186, t = 3.091), non-smoking status (β = 0.175, t = 2.514), non-alcohol consumption (β = 0.163, t = 2.412), and higher perceived cancer risk (β = 0.286, t = 4.274). Conclusion The suboptimal health literacy levels among lung cancer caregivers observed in this sample underscore the potential need for tailored educational interventions. Future programs may consider addressing modifiable factors, particularly focusing on older, less-educated caregivers with health-risk behaviors. These findings provide preliminary evidence for developing targeted strategies to improve caregiver health literacy in similar clinical settings.